Control of Air Conditioning - Avsec, Jurij; Novosel, Urška (University of Maribor Press, 2017)
This book contains theoretical explanations and exercises on moist air thermodynamics and thermodynamic processes with moist air. We concentrated in particular on air-conditioning and cooling tower processes. The book also contains a chapter on heat pumps with both the low-temperature and industrial heat pumps being dealt with. Each chapter in the book is divided into two parts; a short theoretical section followed by exercises. It is intended for students of the control of air conditioning course and for energy technology experts.